2009
DOI: 10.1038/cr.2009.13
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics: heterochromatin meets RNAi

Abstract: The term epigenetics refers to heritable changes not encoded by DNA. The organization of DNA into chromatin fibers affects gene expression in a heritable manner and is therefore one mechanism of epigenetic inheritance. Large parts of eukaryotic genomes consist of constitutively highly condensed heterochromatin, important for maintaining genome integrity but also for silencing of genes within. Small RNA, together with factors typically associated with RNA interference (RNAi) targets homologous DNA sequences and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 130 publications
(175 reference statements)
0
78
0
1
Order By: Relevance
“…In mammals, its establishment at a particular locus is a result of protein interactions and cross talk with multiple silencing mechanisms such as DNA methylation, genomic imprinting and Polycomb group of proteins (PcG) [65,103,110] . The epigenetic profiles across mammalian genomes are very heterogeneous and show a wide range of silencing dynamics.…”
Section: Tgsmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, its establishment at a particular locus is a result of protein interactions and cross talk with multiple silencing mechanisms such as DNA methylation, genomic imprinting and Polycomb group of proteins (PcG) [65,103,110] . The epigenetic profiles across mammalian genomes are very heterogeneous and show a wide range of silencing dynamics.…”
Section: Tgsmentioning
confidence: 99%
“…This RITS complex is analogous to the RISC complex from PTGS. RITS is then directed through siRNA base pair complementarity to a specific locus at which it induces recruitment of Clr4 (histone methyltransferase) and Swi6 (chromo domain binding protein) in order to establish and spread heterochromatin domains [103][104][105] . Human sncRNA-directed TGS is mainly, but not exclusively directed by AGO-1 rather than AGO-2, and is generally triggered by promoter-targeted sncRNAs (Figure 2).…”
Section: Tgsmentioning
confidence: 99%
“…Studies in a variety of systems have identified numerous chromatin-modifying enzymes as well as structural proteins that promote heterochromatin assembly and function. Perhaps the most well-known chromatin modification required for these processes is the methylation of Lys 9 of the N-terminal tail of histone H3 by the Su(var)3-9/Clr4/Kmt1 family of histone methyltransferases, and its recognition by the chromodomains of HP1 family proteins (Lomberk et al 2006;Grewal and Elgin 2007;White and Allshire 2008;Djupedal and Ekwall 2009).…”
mentioning
confidence: 99%
“…Other than DNA methylation and histone modiˆca-tion, non-coding RNA, microRNA, and polycomb group (PcG) protein complex are epigenetic factors that modulate chromatin higher structure and in‰uence the cellular phenotype (20,21). These varieties of macromolecular architectures may regulate and integrate epigenome inheritance.…”
Section: Seiichiroh Ohsakomentioning
confidence: 99%